(untitled) (Kronika Bydgoska, 2010)
Professor Piotr M. Jaśkowski, MD, Ph.D. died on January 6, 2011. In the years 1972-1976, he studied physics at the Nicolaus Copemicus University in Toruń, and next at the Adam Mickiewicz University in Poznań. On Octo- ber 1,1979, he started to work at the Poznań University of Medical Sciences Department of Biophysics. In 1982, having passed the doctoral examination at the University of Medical Sciences he was granted the academic degree of doctor of natural Sciences (biophysics). In 1995, he was granted the post- doctoral degree of medical Sciences. In 2002, he got professorship in medical Sciences. In 2008, he presented his postdoctoral thesis in psychology and was granted the postdoctoral degree in the humanities at the Jagiellonian University. He worked at the Poznań University of Medical Sciences Department of Biophysics (1979-1998). In the years1998-2004, he managed the Department of Psychophysiology at the Casimir the Great University of Bydgoszcz.From 1996 to 2004,he worked as a visiting professor at the Lubeck University Department of Neurology. From 2003, he managed also the Department of Cognitive Psychology at the University of Finance and Management in Warsaw. From 2004 to 2011, he was this university’s vice-president for science. At the same time, in the years 2002-2011, he worked at the Adam Mickiewicz University Faculty of Physics in Poznań. The main research directions of professor Jaśkowski were connected with psychophysiology - cognitive neuroscience.